Changes in Context and Perception of Maximum Reaching Height. (February 2014) - Wagman, Jeffrey B; Day, Brian M
Successfully performing a given behavior requires flexibility in both perception and behavior. In particular, doing so requires perceiving whether that behavior is possible across the variety of contexts in which it might be performed. Three experiments investigated how (changes in) context (ie point of observation and intended reaching task) influenced perception of maximum reaching height. The results of experiment 1 showed that perceived maximum reaching height more closely reflected actual reaching ability when perceivers occupied a point of observation that was compatible with that required for the reaching task. The results of experiments 2 and 3 showed that practice perceiving maximum reaching height from a given point of observation improved perception of maximum reaching height from a different point of observation, regardless of whether such practice occurred at a compatible or incompatible point of observation. In general, such findings show bounded flexibility in perception of affordances and are thus consistent with a description of perceptual systems as smart perceptual devices.